Mengoptimalkan Kinerja Bisnis Dawet Siwalan Hendrosari Melalui Pendekatan Ekonomi Manajerial - Aditya, Alfandi; Wahyuni, Titik; Shofi, M. Hikamus; Firmansyah, Muhammad Yusni Rifqie Insan; Burhan, Umar (Jurnal Bisnis Indonesia, 2024)
Dawet comes from Jepara, Central Java, but is famous for its unique taste in many regions inIndonesia. Dawet Ice from Hendrosari Village, Menganti Gresik District is combined with Siwalanfruit to become Dawet Siwalan Ice (DILAN). DILAN sales are managed from the Siwalan sales centerand focus on educational tourism in Hendrosari. The quality of the resulting taste and its coordinationbetween local and global is an interesting study. This research uses observation methods to collectinformation about the business. Observations show that Es Dawet Siwalan only sells drinks and notfood. In the face of economic globalization, corporate competition and the need for rapid innovation,small and medium enterprises require continuous support from stakeholders for economic recovery.One of the current challenges in increasing productivity and competitiveness is the increase inbeverage imports in Indonesia. So I think local drinks should be reintroduced as a good concept.There are many issues that need to be considered by both the business world and the government. Forexample, using effective marketing strategies to increase beverage sales and optimizing the supplychain to reduce production costs. Implementing risk management will also help companies overcomefuture challenges such as fluctuations in raw material prices and intense competition in the beveragemarket.Keywords: Business; Dawet Siwalan Ice; Application of Managerial Economics.